2021
DOI: 10.3390/ani11051214
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impact of Rotationally Grazed Pastures at Different Management Intensities in South Africa

Abstract: Nitrogen fertilization, irrigation and concentrate feeding are important factors in rotational pasture management for dairy farms in South Africa. The extent to which these factors affect environmental efficiency is subject to current and intense debate among scientists. A three-year field study was conducted to investigate the yield response of different N-fertilizer treatments (0 (N0), 220 (N20), 440 (N40), 660 (N60) and 880 (N80) kg N ha−1 year−1) on grazed pastures and to calculate the carbon footprint (CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The average carbon footprint across all farming systems was 1.36 ± 0.21 kg CO 2 eq kg −1 FPCM, which was in alignment with (Meissner and Ohlhoff, 2022) who reported GHG emissions from milk production in South Africa range between 1.2 and 1.4 kg CO 2 eq kg −1 milk. Smit et al (2021) measured GHG emissions directly from soil in response to N fertilizer treatments in the Western Cape province of South Africa and reported a carbon footprint of 1.3 kg CO 2 eq kg −1 energy corrected milk, for treatments receiving <200 kg N ha −1 year −1 , and a maximum carbon footprint of 2.6 kg CO 2 eq kg −1 ECM when 800 kg N ha −1 year −1 was applied. Compared to similar cradle-to-farmgate lifecycle assessment of GHG emissions studies performed outside South Africa, the average carbon footprint found in our assessment was greater.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average carbon footprint across all farming systems was 1.36 ± 0.21 kg CO 2 eq kg −1 FPCM, which was in alignment with (Meissner and Ohlhoff, 2022) who reported GHG emissions from milk production in South Africa range between 1.2 and 1.4 kg CO 2 eq kg −1 milk. Smit et al (2021) measured GHG emissions directly from soil in response to N fertilizer treatments in the Western Cape province of South Africa and reported a carbon footprint of 1.3 kg CO 2 eq kg −1 energy corrected milk, for treatments receiving <200 kg N ha −1 year −1 , and a maximum carbon footprint of 2.6 kg CO 2 eq kg −1 ECM when 800 kg N ha −1 year −1 was applied. Compared to similar cradle-to-farmgate lifecycle assessment of GHG emissions studies performed outside South Africa, the average carbon footprint found in our assessment was greater.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the growing interest in dairy-based carbon footprint studies globally, assessments for South African pasture-based dairy farming systems are currently absent (Smit et al, 2021;Mazzetto et al, 2022) although livestock accounts for ∼50% of annual CH 4 emissions in South Africa (Department of Forestry, Fisheries and the Environment, 2021). In addition, dairy cattle account for ∼12% of the annually emitted enteric CH 4 from all livestock in South Africa (Tongwane and Moeletsi, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the many avenues of nutrient inputs in dairy pasture systems, overfertilization is likely [8,9]. Pasture productivity deteriorates when fertilizer is applied in excess [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, over-fertilization results in losses through leaching and run-off of nutrients, which impairs water quality at the ground and surface water levels [11,12]. Overfertilizing with N also increases greenhouse gas emissions, particularly nitrous oxide [9]. It is thus important that producers refine fertilizer programs to match crop requirements and consider the amount of soil N that could be mineralized from organic matter [8].…”
Section: Introductionmentioning
confidence: 99%